دور الأميرة أشرف بهلوي السياسي الفعال في القضاء على الحركات الانفصالية في إيران 1941-1946: جمهورية كردستان أو مهاباد - الجابري، عباس حسين; الأعاجيبي، حبيب عمران جادر (مركز ابن العربي للثقافة والنشر, 2021)
ارتبط اسم الأميرة أشرف بهلوي بحوادث مهمة جدا في تاريخ إيران المعاصر وكانت لها أثرها في الواقع السياسي والاجتماعي الإيراني، وخاصة بعد تنازل ولدها رضا شاه بهلوي إلى أخيها محمد رضا في السادس عشر من أيلول 1941 ومساندته في ترسيخ النظام الملكي في إيران. يهدف هذا البحث إلى معرفة الدور السياسي للأميرة أشرف بهلوي في إيران وأن يكون حافزا في تشجيعهم الباحثين على دراسة الشخصيات الإيرانية المؤثرة في إيران طيلة العهد البهلوي الثاني (1941-1979). استعمل الباحث المنهج التاريخي واعتمد في الدراسة على الوثائق الكردية والأجنبية التي أفادت موضوع الدراسة، فضلا عن الكتب العربية والمعربة، والكتب الفارسية ذات العلاقة بموضوع الدراسة. توصل البحث إلى مجموعة من النتائج أهمها: - التعرف على شخصية الأميرة أشرف بهلوي القوية والمؤثرة في البلاط الإيراني التي استطاعت القضاء على الحركات الانفصالية في إيران من خلال سفرها إلى الاتحاد السوفيتي ولقائها بالزعيم جوزيف ستاليم وسحب الدعم السوفيتي لجمهورية مهأباد والقضاء عليها وتثبيت الحكم البهلوي وترسيخه. - الوقوف على معاناة الأقليات في إيران وخاصة القومية الكردية وحرمانهم من أبسط حقوقهم في إيران. - معرفة أسباب إعلان الأقليات في إيران الانفصال عن الحكومة المركزية وتأسيس جمهورية مهأباد ذات الحكم الذاتي. - ضرورة أن تولى الجامعات العراقية قسما خاصا لدراسة الشخصيات الإيرانية المؤثرة في إيران طيلة فترة العهد البهلوي الثاني (1941-1979).
The name of Princess Ashraf Pahlavi has been associated with very important incidents in the contemporary history of Iran and they had an impact on the Iranian political and social reality, especially after the abdication of her son Reza Shah Pahlavi to her brother Muhammad Reza on the sixteenth of September 1941 and his support in the consolidation of the monarchy in Iran. This research aims to know the political role of Princess Ashraf Pahlavi in Iran to provide and encourage researchers to study the influential Iranian personalities in Iran during the second Pahlavi era (1941-1979). The researcher used the historical method and relied in the study on Kurdish and foreign documents that reported the subject of the study, as well as Arabic and Arabized books and Persian books related to the subject of the study that contributed to enriching the study. The research reached a set of results, the most important of which are: - Getting acquainted with the strong and influential personality of Princess Ashraf Pahlavi in the Iranian court, who was able to eliminate the separatist movements in Iran through her travels to the Soviet Union and her meeting with the leader Joseph Stalim, the withdrawal of Soviet support for the Republic of Mahabad and its elimination and the establishment and consolidation of the Pahlavi rule. Standing on the suffering of minorities in Iran, especially Kurdish nationalism, and depriving them of their most basic rights in Iran. - Knowing the reasons for the declaration of minorities in Iran to separate from the central government and the establishment of the Mahabad Autonomous Republic. The necessity for Iraqi universities to assign a special section to study the influential Iranian personalities in Iran throughout the period of the second Pahlavi era (1941-1979).
Keywords: إيران -- أمراء إيران -- جهورية كردستان -- الحركات الانفصالية -- بهلوي، أشرف، ت. 2016 م